(untitled) (Gestão & Regionalidade, 2023)
Based on the assumptions of the 2030 Agenda that the United Nations established for the universalization of water supply and sanitation, this study aims to present for reflection the evaluative elements in the Legal Framework of Basic Sanitation in Brazil, Law 14.026/2020, and recognize and derive its foundations and probable ethical consequences. It is an exploratory and reflective study with a qualitative and documentary basis. Based on the critical analysis, water security is considered fundamental to ensure the sustainability of humankind’s survival on Earth in its multiple aspects. Indeed, implementing well-structured public policies can ensure universal access to the water supply. However, when analyzing the current change in the sanitation regulatory framework in Brazil, methodological, technical, and ethical detachments were detected, suggesting that economically weaker populations were not privileged regarding access to water, making them even more vulnerable.